Interleukin-10 Protects Schwann Cells against Advanced Glycation End Products-Induced Apoptosis via NF-κB Suppression - Xu, Shiqing; Bao, Weijie; Men, Xiuli; Liu, Ying; Sun, Jie; Li, Jing; Liu, Honglin; Cai, Hanqing; Zhang, Wenjian; Lou, Jinning; Peng, Liang (Experimental and Clinical Endocrinology & Diabetes, 2020)
Demyelination resulting from Schwann cell injury is a main pathological feature of diabetic neuropathy, and a key contributor to this process may be inflammation due to advanced glycation end products (AGEs). Therefore, protection by anti-inflammation agents is anticipated. In this study, we showed that interleukin-10 (IL-10), an anti-inflammatory cytokine, inhibits apoptosis of Schwann cells induced by AGEs in vitro. We isolated and cultured Schwann cells from rat sciatic nerves. As detected by flow cytometry, apoptosis of Schwann cells markedly increased following incubation with AGEs for 48 h. However, pretreatment with IL-10 inhibited AGE-induced apoptosis. The effect of IL-10 on NF-κB, which is a very important regulator of inflammation, was also evaluated, and results showed high levels of phospho-NF-κB and nuclear localization of NF-κB in cells incubated with AGEs but low levels of phospho-NF-κB and cytoplasmic localization in the cells incubated with IL-10, indicating the activation of NF-κB by AGEs and inhibition of NF-κB by IL-10. Moreover, incubating Schwann cells with an NF-κB inhibitor (caffeic acid phenethyl ester) for 30 min before adding AGEs mimicked IL-10, lowering the amount of reactive oxygen species and activity of caspase-3 and also decreasing apoptosis in Schwann cells. These results indicate that IL-10 may protect Schwann cells against AGE-induced apoptosis by attenuating oxidative stress via the inhibition of activation of NF-κB.
Keywords: diabetic neuropathy; advanced glycation end products; schwann cell; apoptosis; IL-10